The design of an adaptive tuned vibration absorber - Ainatul Mardiah, Ibrahim (2007)
The harmonic vibration of a machine is an undesirable effect of rotating out-of balance mass within the system. It may influence the machine operation by create unwanted noise and resulting excess wear. However the vibration of the machine can be suppressed by attaching vibration absorber whose natural frequency is tuned to be equivalent to the excitation frequency of the machine. Almost vibration absorber is only effective at particular forcing frequency. A way of overcoming this problem is by designing an adaptive tuned vibration absorber which could adapt itself in response to changes in excitation frequency of machine. This could be realized by varying the stiffness of the spring since the vibration absorber can be simplified as a mass spring system. Due to its variable stiffness capability, it can now be operated at a wide range of frequency by applying a flexibility coefficient method. A practical method on varying the stiffness element is by designing a cantilever beam acting as a spring with a moveable end-mass. The linear movement of the end-mass is controlled by a linear actuator which is connected to the controller. The design requirement of the project is to design a small absorber which can be used in the laboratory and has a capability to track frequency drift approximately ± 50% of its centre frequency of 100 Hz.